Incidence of ipsilateral intra-articular distal radius and scaphoid fractures at Chris Hani Baragwanath and Charlotte Maxeke Academi Hospitals - Richard, Kgabu (My University, 2018)
Ipsilateral distal radius and scaphoid fractures are rare as reported in the literature due to limited research work that has been done on this subject. The literature is populated with case study reports and only two large studies have reported an incidence of 0.7 to 6.5 percent on these fractures [Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine, 2019